2021
DOI: 10.52547/rbmb.10.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxidative Stress, Apoptosis, and Expression of MicroRNA-208a and MicroRNA-1 in Cardiovascular Patients

Abstract: Background: MicroRNA expression signature and reactive oxygen species (ROS) production have been associated with the development of cardiovascular diseases (CVDs). This study aimed to evaluate oxidative stress, inflammation, apoptosis, and the expression of miRNA-208a and miRNA-1 in cardiovascular patients. Methods: The study population included four types of patients (acute coronary syndromes (ACS), myocardial infarction (MI), arrhythmia, and heart failure (HF)), with 10 people in each group, as well as a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…The lowest concentration of GPX and SOD along with highest expression of miRNA-208 activity was observed in the group of heart failure. miRNA-1 was significantly downregulated in HF patients in comparison to other groups [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The lowest concentration of GPX and SOD along with highest expression of miRNA-208 activity was observed in the group of heart failure. miRNA-1 was significantly downregulated in HF patients in comparison to other groups [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the results of molecular docking also exhibited that all of them have good binding properties with core target genes. Clinical studies have shown that the expression of BAX was increased in cardiovascular patients, including arrhythmia [32], and caspase3 variants was susceptible to atrial brillation (AF). Myocardial apoptosis can cause electrical and structural cardiac remodeling [33]; and as the important apoptotic factors, the expression of CASP8, CASP9, BAX was altered in many cardiovascular disease (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of miR-208a in cardiovascular patients is proven to be associated with increased oxidative stress, inflammation, and apoptosis. A recent study showed a significant increase in the expression of miR-208a in heart failure, VA, and myocardial infarction patients when compared to the control group [30]. The increase in miR--208a was in pair with apoptotic and inflammation factors, like BAX and TNF-α, thus revealing miR-208a's potential role in these processes.…”
Section: The Role Of Microrna In Ventricular Arrhythmiasmentioning
confidence: 96%